Perceptions of COVID-19 symptoms, prevention, and treatment strategies among people in seven Arab countries: A cross-sectional study - Feras Jirjees; Muna Barakat; Qamar Shubbar; Bayan Othman; Hamzah Alzubaidi; Hala Al-Obaidi (Elsevier, 2022)
Backgroup: the widespread COVID-19 infection worldwide has resulted in the inability of healthcare facilities to receive all infected patients; therefore, most are treated at home. In addition, factors such as high mortality, types and severity of symptoms, and the prevalence of unreliable information have prompted patients to resort to self-treatment. Objectives: To assess prevention, treatment, degree of symptoms, and sources of information among patients with COVID-19 in Arab countries Method: A cross-sectional study was conducted in seven Arab countries: Algeria, Egypt, Iraq, Lebanon, Libya, Tunisia, and the United Arab of Emirates. People who have recovered from COVID-19 completed the study questionnaire. Score of symptoms during and after COVID-19 infection has been calculated by giving the participants a list of 13 symptoms. Results: A total of 3519 participants completed the survey. Mostly females (68.3%), and aged between 18 and 40 years old (59.4%). Prophylaxis treatments, including vaccines and antibiotics, have been used in around 40% of the participants. The total average score of symptoms during the infection period was found 7.31 ± 3.66 out of 13. However, the symptoms score upon recovery was low (0.48 ± 1.11 score). The significant associations with increased incidence of symptoms during infection were reported with older people, married, divorced or widowed, people with chronic diseases, and obese. Moreover, significant associations with decreased symptoms were reported with those who worked in the health sector, non- or ex-smokers, and vaccinated people. Conclusion: The use of medication and other treatments to prevent infection with COVID-19 was common among the participants in the seven countries. Taking the vaccine was the only effect on the number of symptoms experienced by patients. Although nearly two years have passed since the onset of the disease, there is still a need to raise treatment awareness among patients at home.